THE NARCOTICS ABUSE AND MENTAL HEALTH STATUS AMONG ADOLESCENTS LIVING IN BOARDING HOUSES - Tarmizi, Muhammad Ihsan; Achindri, Belia (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Palembang, 2025)
Background: Narcotic abuse among adolescents living in boarding houses is often closely linked to their psychological conditions and the lack of parental supervision. This study aims to investigate the use of narcotics based on mental health status. Methods: Using a cross-sectional descriptive design, urine samples for testing were collected from 20 adolescents selected through purposive sampling. The instruments used were the SRQ-20 questionnaire for mental health screening and a Rapid Test Multi-Drug (6 parameters) for urine examination. Results: Out of 20 respondents, 2 (10%) were positive for narcotics, and 18 (90%) were negative. Mental health screening results showed that 2 respondents (10%) indicated poor mental health, while 18 (90%) reported good mental health. Crosstab analysis showed that 100% of respondents who tested positive for narcotics were those with poor mental health status, while 100% of respondents with good mental health showed negative narcotic results. Conclusion: The abuse of drugs in this population occurs in individuals experiencing mental health problems, supporting the self-medication hypothesis. Therefore, the integration of mental health screening services in adolescent living environments is needed as a preventive measure.